Design and development of 5-(4H)-oxazolones as potential inhibitors of human carbonic anhydrase VA: towards therapeutic management of diabetes and obesity. Issue 7 (3rd May 2022) - Das Mahapatra, Amarjyoti; Queen, Aarfa; Yousuf, Mohd; Khan, Parvez; Hussain, Afzal; Rehman, Md. Tabish; Alajmi, Mohamed F.; Datta, Bhaskar; Hassan, Md. Imtaiyaz
Abstract: Inhibitors of carbonic anhydrase (CAIs) hold promise for addressing various diseases, including cancer, diabetes, and other metabolic syndromes. CAV is the only isoform present in the mitochondria and is considered a potential drug target for obesity. In this work, we have developed C2, and C4 substituted oxazole-5(4H)-one derivatives as a new scaffold for the selective inhibition of human carbonic anhydrase VA (hCAVA). Synthesized compounds were characterized by 1 H NMR, 13 C NMR, and LC-MS mass spectrometry and subsequently evaluated for in vitro hCAVA inhibition. Two compounds, 4 and 5 showed a considerably higher binding affinity for hCAVA in comparison to the hCAII. Further, cell-based studies showed that these compounds decrease the expression of CAVA and GLUT4 in adipocytes and non-toxic to HEK293 cells. The present work opens a platform for the use of oxazole-5(4H)-ones and holds promise for further refinement of potent and selective hCAVA inhibitors. Communicated by Ramaswamy H. Sarma